Food Policy Research Capacity Indicators (FPRCI), 2010-2019 - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
Food policy research plays a crucial role in guiding agricultural transformation in developing countries. To achieve food security goals, countries need to strengthen their capacity to conduct food policy research. Strong local policy research institutions help shaping evidence-based policymaking. Measuring national capacity for food policy research is important for identifying capacity gaps in food policy research and guiding the allocation of resources to fill those gaps. “Food policy research capacity” is defined as the ability to do socioeconomic or policy-related research in the areas of food, agriculture, nutrition, or natural resources. To measure this capacity, the International Food Policy Research Institute (IFPRI) has developed a set of indicators for the quantity and quality of policy research at the country level. IFPRI created the Food Policy Research Capacity Indicators (FPRCI) database in 2010 and has since continued to expand and refine it. Data are currently collected for 33 countries; data for Myanmar was added in 2017. A consistent methodology is followed to enable a comparison of values across time and countries. The database was most recently updated with numbers for 2019. Analysts/researchers counts the professionals employed at local organizations whose work involves food policy research or analysis. To introduce some uniformity, IFPRI also presents a modified quantification of this headcount: full-time equivalent analysts/researchers with PhD. To obtain an indicator of per capita food policy research capacity, this research capacity is then divided by the country’s rural population (full-time equivalent researchers per million rural residents). This helps to illustrate the impact of local food policy research in a country. This indicator was last updated in 2015. The quality of a country’s food policy research capacity is estimated by tallying the number of relevant international publications in peer-reviewed journals over a five-year period. IFPRI views this as a reflection of the local enabling intellectual environment for food policy research. This indicator allows for comparison across countries, as it ensures an internationally accepted standard of quality for publications. The final indicator is derived by dividing the number of international publications by the number of full-time equivalent researchers with a PhD, providing a measure of productivity.